Measuring Positive Emotion Outcomes in Positive Psychology Interventions: A Literature Review. (January 2021) - Moskowitz, Judith T.; Cheung, Elaine O.; Freedman, Melanie; Fernando, Christa; Zhang, Madelynn W.; Huffman, Jeff C.; Addington, Elizabeth L.
Accumulating evidence for the unique social, behavioral, and physical health benefits of positive emotion and related well-being constructs has led to the development and testing of positive psychological interventions (PPIs) to increase emotional well-being and enhance health promotion and disease prevention. PPIs are specifically aimed at improving emotional well-being and consist of practices such as gratitude, savoring, and acts of kindness. The purpose of this narrative review was to examine the literature on PPIs with a particular focus on positive emotion outcomes. We evaluated the evidence on the effects of PPIs on positive emotion specifically, and discussed the range of evidence regarding the relative responsiveness of emotion measures to PPIs in order to gain a better understanding of the specific emotional pathways through which PPIs influence psychological and physical well-being. We conclude with recommendations for best evaluating effects of PPIs on positive emotion outcomes.